Fishery resource monitoring of the East China Sea via environmental DNA approach: a case study using black sea bream (Acanthopagrus schlegelii) - Zhang, Haobo; Zhou, Yongdong; Zhang, Hongliang; Gao, Tianxiang; Wang, Xiaoyan (Frontiers in Marine Science, 2022)
Understanding fish stock distribution is crucial in the context of sustainable fishery development. Traditional approaches such as net catching, mark recapturing, and visual counting are often time-consuming, less effective, and prone to subjective bias. Recently, environmental DNA (eDNA) technology has made up for the shortcomings of traditional fishery resource survey methods and has been widely used for species monitoring, biodiversity assessment, and biomass estimation. In this study, the eDNA method was used to analyze the potential distribution range of the black sea bream (Acanthopagrus schlegelii) in the East China Sea. The black sea bream-specific primers and probe were designed and applied in the current study. Results showed high black sea bream eDNA concentrations in Dasha fishing ground, Yangtze Estuary fishing ground, and Zhoushan fishing ground. Higher concentrations of black sea bream eDNA were found in water depths approximately 30–40 m. The eDNA hotspots were mainly concentrated at 29°N–33°N, 122°E–125°E, but no significant differences in horizontal or vertical distributions were observed. Temperature is a critical factor in the presence and black sea bream eDNA among environmental variables in the correlation analysis. In addition, a linear formula between environmental factors and the black sea bream eDNA concentration of black sea bream was predicted, which may be helpful for future fishery resource surveys. To summarize, the present paper provides a new idea for marine resource surveys. It also affords a method and theoretical basis for applying the eDNA technology in fishery surveys, which is expected to become an essential tool for fishery resource surveys in the future.